Ovarian and endocrine response following pretreatment with human chorionic gonadotrophin and estradiol valerate in PMSG treated crossbred cows - KHARCHE, S D; MAJUMDAR, AC; AGARWAL, S K; SHARMA, G TARU (The Indian Journal of Animal Sciences, 2011)
The effect of heO and estradiol valerate on endocrine profiles and superovulatory response of crossbred cows treated with PMSG was studied. Cyclic crossbred cows (22) were treated with a single i/m administration of prostaglandin F2 0:. (2 ml prosolvin). The 18 animals that exhibited estrus within 72-96 h prostaglandin F2 ex administration were selected for the superovulatory treatments. In treatment 1, cattle (10) were administered 250 IU heG i/m on day 9 (day o=estrus), 2 mg estradiol valerate on day 10, and 2000 ill PMSG on day 11 of the estrous cycle. Treatment 2 animals (8) were not pre-treated and were administered 2000 IU PMSG on day 11. Both groups were treated with PO F2 a 48 h after PMSG treatment. The animals were exposed to a teaser bull in the morning and evening to aid detection of estrus. The interval from prostaglandin treatment to estrus was 43.5Â±2.05 h for treatment 1 and 52.8Â±4.22 h for treatment 2. The crossbred cows were inseminated 3 times at 12 h intervals during estrus and embryos collected non-surgically at day 8 of the superovulatory estrus. The pretreatment of heG and estradiol valerate in a PMSG treated crossbred cows resulted in a significantly higher levels of progesterone and estradiol 24 h after administration of heG and estradiol valerate. Treatment 1 crossbred cows also showed an increase in the number of corpora lutea, total ova and transferable embryos recovered as compared to treatnlent 2. The results indicated that the pretreatment with heG and estradiol valerate in a PMSG treated crossbred cows showed a significant increase in plasma level of progesterone and estradiol and an improvement in the yield of transferable embryos from cycling crossbred cows. Â